Thermal decay of two-spinon bound states in quasi-two-dimensional triangular antiferromagnets - Pomponio, Ignacio Luciano (2024)
We analyze the temperature evolution of the anomalous magnetic spectrum of the spin-1/2 triangular quantum Heisenberg antiferromagnet, which is proximate to a quantum phase transition leading to a spin-liquid phase. Recently, its low-energy excitations have been identified with two-spinon bound states, well defined in an ample region of the Brillouin zone. In this work, we compute the thermal magnetic spectrum within a Schwinger boson approach, incorporating Gaussian fluctuations around the saddle-point approximation. In order to account for a finite Néel temperature TN , we incorporate an exchange interaction between triangular layers. As temperature rises, the dispersion relation of the two-spinon bound states, representing single-magnon excitations, remains unchanged but becomes mixed with the thermally activated spinon continuum. Consequently, a crossover occurs at a temperature T∗ ≃ 0.75TN , defining a terminated Goldstone regime between T ∗ and TN , where only the magnons close to the Goldstone modes survive as well-defined excitations, up to the Néel temperature. Our results support the idea that the fractionalization of magnons near a transition to a disordered phase can be extended to more realistic quasi-two-dimensional frustrated antiferromagnets.